Metabarcoding reveals a high diversity and complex eukaryotic microalgal community in coastal waters of the northern Beibu Gulf, China - Wang, Chaofan; Gu, Junning; Li, Weiguo; Wang, Jian; Wang, Zhaohui; Lin, Qiuqi (Frontiers in Microbiology, 2024)
Beibu Gulf is an important semi-enclosed bay located in the northwestern South China Sea, and is famous for its high bio-productivity and rich bio-diversity. The fast development along the Beibu Gulf Economical Rim has brought pressure to the environment, and algal blooms occurred frequently in the gulf. In this study, surface water samples and micro-plankton samples (20-200 µm) were collected in the northern Beibu Gulf coast. Diversity and distribution of eukaryotic planktonic microalgae were analyzed by both metabarcoding and microscopic analyses. Metabarcoding revealed much higher diversity and species richness of microalgae than morphological observation, especially for dinoflagellates. Metabarcoding detected 144 microalgal genera in 8 phyla, while microscopy only detected 40 genera in 2 phyla. The two methods revealed different microalgal community structures. Dinoflagellates dominated in microalgal community based on metabarcoding due to their high copies of 18s rRNA gene, and diatoms dominated under microscopy. Altogether 48 algal bloom and/or toxic species were detected in this study, 34 species by metabarcoding and 19 species by microscopy. Our result suggested a high potential risk of HABs in the Beibu Gulf. Microalgal community in the surface water samples demonstrated significantly higher OTU/species richness, alpha diversity, and abundance than those in the micro-plankton samples, although more HAB taxa were detected by microscopic observations in the micro-plankton samples. Furthermore, nano-sized taxa, such as those in chlorophytes, haptophytes, and chrysophyceans, occurred more abundantly in the surface water samples. This study provided a comprehensive morphological and molecular description of microalgal community in the northern Beibu Gulf.